Data-driven analysis of the real-time electricity price considering wind power effect - Shengjie Yang; Xuesong Xu; Jiangang Liu; Weijin Jiang (Energy Reports, 2020)
The electricity price is the sensitive signal of the supply-demand balance and some other market incidents. The analysis of the price data can provide plenty of the market information. It is helpful for the participants to understand the market and improve future strategies. However, most of the forecast models eliminate the details to reduce the structural risk for generality. In this paper, the data-driven analysis is proposed to explore the PJM electricity price in detail. The price time series is decomposed into different components. Each component is modeled and tested by the statistical method to illustrate the hidden pattern of the fluctuation, so that there can be reasonable interpretation about the market. The relationship between the price and the wind power is numerically detected through the heterogeneity of the price time series. The paper demonstrates the data-driven method to mine information and achieve the analysis of electricity market.
Keywords: 330; Wind power; Electricity market; Heterogeneous volatility; Real-time price; Time series